Synovial Sarcoma of the Wrist in Pediatric Patient: Case Report - Andini, Suci Nurul; Budi, Muhamad Naseh Sajadi (Jurnal Riset Kedokteran, 2025)
Abstract. Synovial sarcoma is a rare type of soft tissue sarcoma, accounting for approximately 5% of all cases and frequently occurring in adolescents and young adults. It most commonly affects the extremities and is characterized by its aggressive behavior, with a high propensity for local recurrence and distant metastasis. This case report aims to discuss the diagnosis, treatment, and postoperative outcomes of an 11-year-old girl with synovial sarcoma of the right wrist. The patient underwent limb salvage surgery, including wide excision of the affected ulna and tendon reconstruction, followed by adjuvant chemotherapy and radiotherapy. Postoperatively, the patient showed significant improvements in pain, function (M-DASH score), and range of motion over a three-month period, with no signs of infection or disease recurrence.  Although the patient showed significant improvement in pain and functional ability within three months postoperatively, long-term follow-up is essential to monitor for recurrence or metastasis and to assess ongoing functional recovery. This case emphasizes the importance of a multidisciplinary approach in the management of synovial sarcoma, particularly in young patients. Abstrak. Synovial sarcoma adalah jenis langka dari sarkoma jaringan lunak yang mencakup sekitar 5% dari semua kasus dan sering terjadi pada remaja serta dewasa muda. Kondisi ini paling sering menyerang ekstremitas dan ditandai dengan perilaku agresif, memiliki kecenderungan tinggi untuk kambuh secara lokal dan menyebar ke tempat yang jauh. Laporan kasus ini bertujuan untuk membahas diagnosis, pengobatan, dan hasil pascaoperasi pada seorang anak perempuan berusia 11 tahun dengan synovial sarcoma di pergelangan tangan kanan. Pasien menjalani operasi limb salvage, termasuk eksisi luas pada ulna yang terkena serta rekonstruksi tendon, diikuti dengan kemoterapi dan radioterapi adjuvan. Secara pascaoperasi, pasien menunjukkan perbaikan yang signifikan dalam hal nyeri, fungsi (skor M-DASH), dan rentang gerak dalam tiga bulan, tanpa tanda-tanda infeksi atau kekambuhan penyakit. Meskipun pasien menunjukkan perbaikan yang signifikan dalam hal nyeri dan kemampuan fungsional dalam tiga bulan pascaoperasi, tindak lanjut jangka panjang sangat penting untuk memantau kekambuhan atau metastasis serta mengevaluasi pemulihan fungsional yang berkelanjutan. Kasus ini menekankan pentingnya pendekatan multidisiplin dalam penanganan synovial sarcoma, terutama pada pasien muda.